Trends in Transcatheter Edge-to-Edge Mitral Valve Repair Over a Decade: Data From the MiTra ULM Registry - Nita, Nicoleta; Schneider, Leonhard; Dahme, Tilman; Markovic, Sinisa; Keßler, Mirjam; Rottbauer, Wolfang; Tadic, Marijana (Frontiers in Cardiovascular Medicine, 2022)
Objective This study sought to determine the potential change in trends in the baseline characteristics of patients with symptomatic severe mitral regurgitation who underwent transcatheter edge-to-edge mitral valve repair (M-TEER) over the last decade in a high-volume center. Methodology The investigation included 942 symptomatic patients with moderate-to-severe and severe mitral regurgitation who underwent transcatheter edge-to-edge repair (TEER) at our institution between January 2010 and March 2021. Patients were divided into quintiles and compared separately. Results Patients treated in the last quintile had significantly lower surgical risk (Euro Score 7.2 ± 6.8% in the last quintile vs. 10.9 ± 9.4% in the first quintile, p < 0.001), better New York Heart Association (NYHA) status (NYHA IV 14% in the last quintile vs. 40% in the first quintile, p < 0.001), lower NT-pro-BNP, and smaller left ventricle diameter than patients who were treated in the first quintile. There was no difference in age between quintiles. However, an invasive hemodynamic assessment did not show significant changes over the last decade (sPAP 51.35 ± 16.2 mmHg in the first quintile vs. 51.02 ± 14.5 mmHg in the last quintile, p = 0.90, pulmonary capillary wedge V wave 30.7 ± 14.8 mmHg in the first quintile vs. 27.4 ± 10.3 mmHg in the last quintile, p = 0.40). There is a significant trend of a gradually increasing proportion of patients with degenerative mitral regurgitation (MR) over the last 10 years (p < 0.001). The experience gained in the M-TEER procedure brought a significant reduction in fluoroscopy time and hospitalization duration. Medical therapy significantly changed over the last decade in terms of higher use of angiotensin receptor blockers (ARBs), lower use of angiotensin-converting enzyme inhibitors (ACEIs), and the introduction of angiotensin receptor-neprilysin inhibitors (ARNIs). Conclusion Patients undergoing the M-TEER procedure nowadays have lower surgical risk and are treated before they develop a significant left ventricular (LV) remodeling than before. The increasing expertise on the procedure over the last decade led to a rising number of patients with complex degenerative pathology being treated.